PENGARUH BELANJA DAERAH, PMDN, DAN PMA TERHADAP PERTUMBUHAN EKONOMI DI PULAU JAWA - Saputri, Karina Dewi; Ananda, Candra Fajri (Journal of Development Economic and Social Studies, 2023)
The objective of this research is to analyze the effects of regional expenditures, domestic investments, and foreign investment on the economic growth of all provinces in Java during the 2006—2021 period. Using panel data of six provinces across the sixteen-year period analyzed through panel data regression, this study finds that regional expenditures, domestic investment, and foreign direct investment positively and significantly affect the economic growth of all provinces in Java during the 2006—2021 period, both partially and simultaneously. Regional spending and domestic investment have a direct effect in the year concerned on economic growth, while foreign investment has an effect in a two-year lag. This happens because the level of ease of doing business and investing in Indonesia is still low, so that local governments together with the central government must coordinate more to make regulations for ease of investment, especially in areas on the Java.